Nobody knows you're here - Greenwood, Bryn (Podium Publishing, 2025)
"Beatrice is about to lose everything when a kind stranger offers her a cup of coffee and a job. It seems like a promise of a better life . . . until she wakes up under lock and key in an isolated mansion in the woods. On orders from a shadowy criminal organization, armed jailers make the rules for their captives, enforcing them with unflinching violence. Beatrice has always been a "nice girl," but that won't save her now. Nobody helped her when she lost her job, her car, and her home, and nobody's coming to give back her freedom. The only person she can rely on is herself. And now, several child hostages are relying on her too. When the situation gets more dire -- deadly even -- Beatrice has to become the hero she and her fellow prisoners need. To escape she'll have to outsmart her captors and do terrible things that would horrify her former self. If she succeeds, there's no telling who she'll be when the ordeal comes to an end." --